A retrospective cross-sectional study of association between triglyceride-glucose index and carotid atherosclerosis - Guo, Congfang; Li, Mingming; Wang, Lili; Bai, Yuting; Rong, Yudong; Zhang, Minying; Guo, Fenghua; Guo, Xiang; Guo, Jie; Zhang, Li; Zhao, Yiyan (Frontiers in Cardiovascular Medicine, 2025)
BackgroundThe triglyceride-glucose (TyG) index, a simple surrogate marker of insulin resistance (IR), has been associated with cardiovascular risk factors and atherosclerosis. However, its relationship with carotid atherosclerosis (CA), including carotid intima thickening (CMT), plaques, and stenosis, remains inadequately studied in the general population.PurposeThis study aimed to evaluate the association between the TyG index and CA.MethodsA retrospective cross-sectional study was conducted among 8,600 participants undergoing health checkups and carotid ultrasonography. CA was defined as the presence of CMT, plaques, or stenosis (>50%). The TyG index was calculated using fasting triglycerides and glucose levels. Multivariate logistic regression and subgroup analyses were performed to assess the association between the TyG index and CA. We constructed fitting curves to evaluate the dose–response relationship between the TyG index and CA in different subgroups. All statistical analyses were executed using R Statistical Software and the Free Statistics analysis platform.ResultsThe TyG index was positively associated with CA (OR = 1.22, 95% CI: 1.08–1.38, P = 0.003), plaques (OR = 1.28, 95% CI: 1.12–1.47, P < 0.001), and stenosis (OR = 2.49, 95% CI: 1.86–3.32, P < 0.001), but not with CMT. Subgroup analyses revealed stronger associations in younger individuals (<49 years), males, and those without hypertension, dyslipidemia, or hyperglycemia. A nonlinear relationship between TyG and CA was observed in lean/normal-weight individuals, with a threshold effect at TyG = 8.112. We found that if TyG below 8.112, each unit increasing in TyG reduced CA risk (OR = 0.26, 95% CI: 0.07–0.96, P = 0.043), while above it, the risk increased significantly (OR = 1.65, 95% CI: 1.06–2.57, P = 0.025) in this study. Linear relationships between TyG index and CA were showed in different subgroups stratified by age, gender and different metabolic conditions and overweight/obesity individals.ConclusionThe TyG index is a significantly association of CA, particularly in high-risk subgroups. The TyG index shows promise for CA risk stratification. Emphasizing the need for targeted interventions in specific populations ahead of time. The TyG index may complement existing tools, but further prospective validation is needed to assess its incremental value.